Scrutinize the Taxonomical Identity of Green Edible Russula from Sulawesi (Indonesia) - Nurhayat, Oktan Dwi; Putra, Ivan Permana; Riffiani, Rini; Taridala, Sitti Aida Adha; Arif, Zulhan (HAYATI Journal of Biosciences, 2025)
Russula Pers. (Basidiomycota) is recognized as one of the most widely distributed macrofungi globally. This genus includes several edible species with distinct color variations, such as R. cyanoxantha. However, in Indonesia, knowledge of this species remains limited as colourful mushrooms are often mistakenly considered poisonous. During a fungus expedition in Southeast Sulawesi, we collected a green edible wild mushroom consumed by locals. Our study aimed to verify the taxonomic classification of our specimens through morphological and molecular analysis. The fresh basidiomata were examined based on their macroscopic and microscopic characteristics. Molecular analysis using ITS 1/2 sequences was conducted to construct a phylogenetic tree. Our findings identified the green mushroom as R. cyanoxantha (Schaeff.) Fr. (Synonym: R. lilacina). Morphologically, our specimens can be distinguished from R. virescens by their smooth cap. They differ from R. aeruginea and R. heterophylla by having flexible, persistent gills. Additionally, our R. cyanoxantha specimen BO24636 can be separated from R. dinghuensis and R. subpallidirosea by their forked gills near the stalk. A BLAST comparison revealed a 96% similarity to R. lilacina from Thailand as the closest match. The phylogenetic tree (Maximum Likelihood) placed our specimens within the R. lilacina group (BS value 99%). Our research contributes to the taxonomic understanding of this edible wild green macrofungi in Indonesia, and future studies should explore its nutritional composition.